KOMUNIKASI PERSUASIF DALAM POLA KEPEMIMPINAN HINDU DI PC KMHDI KENDARI PROVINSI SULAWESI TENGGARA - Darmaputri, Putu Aricha; Lestawi, I Nengah; Nerawati, Ni Gusti Ayu Agung (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
PC KMHDI Kendari organization is a national scale Hindu student organization that functions as a unifying forum and means of education for Hindu student cadres in Kendari City. This study aims to examine the practice of persuasive communication in Hindu leadership patterns in the PC KMHDI Kendari environment by focusing on the implementation of the Asta Brata concept and the practice of Tri Hita Karana values. This research uses a qualitative method with a case study approach, where data is collected through in-depth interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman model. The results showed that the Chairman of PC KMHDI Kendari applied all elements of Asta Brata in his leadership. Persuasive communication by leaders is also reflected in the implementation of the values of the Tri Hita Karana teachings, covering the areas of Parhyangan, Pawongan, and Palemahan, which can strengthen the spiritual and social dimensions of organizational members. The conclusion of this study is that persuasive communication based on Hindu values is an effective foundation in building awareness, empathy, and active involvement of cadre members in the organization, and shows that spiritual value-based leadership can strengthen organizational unity and sustainability.